Antagonism of Pseudomonas fluorescens from plant roots to Rigidoporus lignosus pathogen of rubber white roots in vitro - NURHAYATI DAMIRI; MULAWARMAN MULAWARMAN; RAHIM S EFFENDI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Damiri N, Mulawarman, Effendi RS. 2019. Antagonism of Pseudomonas fluorescens from plant roots to Rigidoporus lignosus pathogen of rubber white roots in vitro. Biodiversitas 20: 1549-1554. Indonesia's rubber productivity is still relatively low. This low productivity of rubber can be caused by many factors such as the attack of Rigidoporus lignosus. This study aims to explore antagonistic bacteria from the plant roots and test their antagonism ability to R. lignosus at the laboratory level. This research was conducted at the Laboratory at the Faculty of Agriculture, Sriwijaya University, Indralaya Ogan Ilir District, South Sumatra, Indonesia. Corporate and bacterial isolations are carried out by serial dilution method. In-vitro testing of antagonistic bacteria was carried out using the dual-culture technique method on sterile PDA media by direct opposition between R. lignosus culture and antagonistic bacteria explored. Results of the study showed that a number of bacterial isolates existed there, namely 11 bacterial isolates belonging to Pseudomonas fluorescens, four from turmeric roots, three from the roots of rubber seedlings, two from galangal roots and two from the roots of yielding rubber plants. P. fluorescens from roots of turmeric, rubber seedlings, rubber, and galangal was able and had the potential to be developed as biopesticide to control R. lignosus. The best isolate in suppressing the growth and development of R. ligonosus is P. fluorescens isolates from the roots of turmeric and those of rubber seedlings (isolates of C, B, and G).